Quantitative validation of the n-butanol sniffin’ sticks threshold pens. - Denzer, Melanie; Gailer, Stefan; Kern, David W.; Schumm, L. Philip; Thürauf, Norbert; Kornhuber, Johannes; Büttner, Andrea; Beauchamp, Jonathan (Chemosensory Perception, 2014)
Odorant pens are used by medical practitioners and researchers to assess olfactory dysfunction. Despite their routine use, there are currently no data on the gas-phase odorant concentrations released from the pen tips or whether these concentrations scale linearly with the aqueous-phase concentrations inside the pens. The commercially available Sniffin’ Sticks odor threshold test containing n-butanol was chosen for evaluation. The gas-phase concentration of n-butanol at the tip of each pen was measured directly in a new set of pens via proton-transfer-reaction mass spectrometry (PTR-MS). Measurements were additionally made on the same pens after 6 months and two older pen sets, namely a 3-year-old (used) and 4-year-old (new) set. Furthermore, application-related tests were made to determine the performance of the pens during routine use and under stress. These data demonstrate that the gas-phase n-butanol concentrations of the threshold pens are linear over the entire set, both for brand-new pens and 6 months later; this reflects the expected performance that was previously only assumed. Furthermore, the application–simulation tests demonstrated a good performance of the pens when used according to their intended protocol. Measurements of the older pen sets suggest that storage conditions are more critical than usage for pen stability. The present findings confirm that the n-butanol odorant pens are an appropriate tool for threshold testing, provided they are stored and handled correctly.<br